Prevention of acute gastric erosions in the rat by novel semi-synthetic amphipathic analogues of pepstatin. Issue 11 (November 1988) - Huddy, S P; Patel, G; Heywood, G C; Austen, B M; Hermon-Taylor, J
Abstract : Pepstatin is a potent aspartyl proteinase inhibitor which is virtually insoluble in physiological media. Five semi-synthetic amphipathic analogues of pepstatin, prepared by N terminal substitution of native pepstatin with hydrophilic oligopeptides, have been assessed for their ability to protect the mucosa in two animal models of acute gastric erosions. Concentrations of approximately 90 pmol/mg were achieved in the rat gastric mucosa after oral administration of a 20 mmol solution. These levels are theoretically adequate to inhibit all pepsin like proteinase activity (including zymogens). Each pepstatin analogue was tested by intragastric administration in a controlled hypotension/luminal acid animal model of acute gastric erosions in a group of six animals. All the inhibitors tested produced marked mucosal protection, as measured by a mucosal damage index, compared with control animals (control mean 241, range 100-420; Pepstatinyl-Gly-Orn-Orn-Cys (10 mmol) mean 3, range 0-8, p less than 0.01; Pepstatinyl-Gly-Cysteic acid-Cysteic acid (10 mmol) mean 5, range 0-21, p less than 0.01; Pepstatinyl-Gly-Lys-Lys (10 mmol) mean 18, range 0-60, p less than 0.01; Pepstatinyl-Gly-Cysteic acid-Cysteic acid (1 mmol) mean 24, range 0-86, p less than 0.01; Pepstatinyl-Gly-Orn-Orn-Cys (1 mmol) mean 57, range 0-116, p less than 0.01; Pepstatinyl-Gly-Asp-Asp (1 mg/ml suspension) mean 68, range 19-126, p less than 0.01; Pepstatinyl-Arg-OMe (1 mmol) mean 93, range 4-142, p less than 0.05, Pepstatinyl-Gly-Lys-Lys (1 mmol) mean 157, range 70-286, NS). In a platelet activating factor/20% luminal ethanol model of erosions the pepstatin analogues again provided mucosal protection although this only reached statistical significance for one of three compounds tested.